Scrooge and significant moral change. Issue 2 (3rd April 2019) - Knobel, Angela
ABSTRACT: Virtue theorists commonly assert that significant moral change, such as the cultivation of a virtue or the elimination of a vice, can only occur over a prolonged period of time. Many scholars who make this claim also accept the comparison between virtues and skills. In this article I argue that if one accepts the comparison between virtues and skills, there should be instances in which significant moral change can occur relatively quickly.